Pengaruh Penambahan Bubuk Daun Kelor (Moringa oleifera L.) dan Suhu Proses Pemanasan terhadap Karakteristik Body Scrub - Gitariastuti, Ni Ketut; Mulyani, Sri; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
Body scrub is a product that works to remove dead skin cells and open pores so the skin becomes brighter and whiter. This study aims to determine the effect of the moringa leaf powder addition and heating process temperature on the characteristics of body scrub and determine the percentage of the addition of moringa leaf powder and the best heating process temperature to produce a body scrub. This study uses a randomized block design with two factors. The first factor is the percentage addition of moringa leaf powder and the second factor is the temperature of the heating process. The first factor consists of 3 levels namely 4, 5 and 6% while the second factor consists of 2 levels namely 65 o C and 70 o C. The results of the study at the 6th week of storage showed that the addition of moringa leaf powder affected viscosity, spreadability power and adhesion power but did not affect the pH and overall acceptance of the body scrub. The temperature of the heating process does not affect the pH, viscosity, spreadability power, adhesion power and overall acceptance of the body scrub. Addition of 4% of moringa leaf powder and 65 o C of the heating process temperature was the best treatment for body scrub with characteristics at the 6th week of storage as follows: pH 4.8, viscosity 10307 cp, spreadability power 5.2 cm, adhesion power 36.75 seconds and separation ratio = 1. Keywords : body scrub, moringa leaf, heating process temperature